2023
DOI: 10.1093/plphys/kiad160
|View full text |Cite
|
Sign up to set email alerts
|

Colorful hues: insight into the mechanisms of anthocyanin pigmentation in fruit

Abstract: Anthocyanin is a vital indicator for both fruit nutritional and commercial value. Anthocyanin accumulation is a surprisingly complicated process mediated by multiple networks associated with genetic, developmental, hormonal, and environmental factors. Transcriptional regulation along with epigenetic regulation constitutes the dominant molecular framework for anthocyanin biosynthesis. Here, we focus on current knowledge on regulatory mechanisms of anthocyanin accumulation, with emphasis on the latest progress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 173 publications
0
14
0
Order By: Relevance
“…Anthocyanins are secondary metabolites induced by environmental stimuli and developmental signals (Ubi, 2004; Yang et al, 2012a; Zhao et al, 2023). Hormones affect anthocyanin biosynthesis, as applying JA, ethylene, and ABA to most plants promotes anthocyanin production, while GA and auxin hinder anthocyanin accumulation (Loreti et al, 2008; Das et al, 2012; Li and Ahammed, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthocyanins are secondary metabolites induced by environmental stimuli and developmental signals (Ubi, 2004; Yang et al, 2012a; Zhao et al, 2023). Hormones affect anthocyanin biosynthesis, as applying JA, ethylene, and ABA to most plants promotes anthocyanin production, while GA and auxin hinder anthocyanin accumulation (Loreti et al, 2008; Das et al, 2012; Li and Ahammed, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Hormones regulate almost every aspect of plant growth and development, including anthocyanin biosynthesis (An et al, 2020a; Li and Ahammed, 2023; Zhao et al, 2023). Among them, jasmonic acid (JA) plays a role in anthocyanin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Anthocyanins, as a class of plant secondary metabolites, play a crucial role in plant growth and development, particularly in flower and fruit coloration. 5 They also serve as a response mechanism against both biotic and abiotic stressors. 6 In addition, these pigments hold significant benefits for human health, as they have been associated with the prevention of neurological and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The difference of skin color between purple and yellow passion fruits was primarily attributed to the varying levels of anthocyanins . Anthocyanins, as a class of plant secondary metabolites, play a crucial role in plant growth and development, particularly in flower and fruit coloration . They also serve as a response mechanism against both biotic and abiotic stressors .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, molecular engineering has enabled production of anthocyanins in non-anthocyanin plants [9]. Studies have also identified the involvement of epigenetic mechanisms in anthocyanin biosynthesis and degradation [10,11]. Some fruits naturally exhibit red pigmentation [12] and are therefore preferential models to study red colour biochemical and phenotypical expression.…”
Section: Introductionmentioning
confidence: 99%